Effects of combining functional exercises with exercise training on daily physical activities and functionality in patients with COPD: A protocol for a randomized clinical trial - De Lima, Fabiano Francisco [UNESP]; Camillo, Carlos Augusto; Grigoletto, Isis [UNESP]; Uzeloto, Juliana Souza [UNESP]; Vanderlei, Franciele Marques [UNESP]; Ramos, Dionei [UNESP]; Ramos, Ercy Mara Cipulo [UNESP] (Springer Nature, 2019)
Introduction: Functional training has been shown to be a viable alternative for the elderly and patients with chronic obstructive pulmonary disease (COPD). However, whether the combination of this type of training with aerobic and resistance training, commonly performed in pulmonary rehabilitation (PR) programs, induces more pronounced effects on daily physical activities and functionality remains unclear. The aims of the study will be to evaluate the short-term and sustained effects of the combination of a functional circuit program with a training program consisting of aerobic and resistance exercise. Methods: In this randomized controlled trial, patients with COPD will be randomly assigned (1:1:1) to an 8-week training program to follow one of the three a priori defined groups: (I) resistance and aerobic and functional exercises, (II) a conventional program including only resistance and aerobic exercises, or (III) a usual care program. Patients will be evaluated before and upon completion of 8 weeks of training regarding physical activity in daily life (PADL) using an activity monitor (accelerometer), activities of daily living (London Chest Activity of Daily Living), functional exercise capacity (6-minute walk test), and muscle strength (dynamometry). Additionally, the sustained effects of the interventions will be evaluated 22 weeks after commencing the study. Discussion: The inclusion of a protocol of functional physical training in the training conventionally performed by patients with COPD as an alternative to increase PADL and functionality may provide subsidies for the treatment of these patients, representing an advance and impacting on the physical training of patients with COPD. Trial registration: Brazilian Clinical Trials Registry (ReBEC) ID: RBR-3zmh3r. Registered: March 7, 2018.
Keywords: Chronic obstructive pulmonary disease; Exercise training; Follow-up; Physical activity levels